Analisis Pelaksanaan Utang Piutang Emas Dalam Perspektif Ekonomi Islam - Femmy Sentriani; Desi Isnaini; Citra Liza (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine the implementation of gold debts and receivables in Ujung Pulau Village based on an Islamic economic perspective. The type of research used is field research. Data collection techniques use observation, interviews and documentation methods, as well as data analysis techniques using a qualitative descriptive approach. The subjects in this research are the givers and recipients of gold debts and receivables. The results of the research show that the implementation of gold debts and receivables in Ujung Pulau Village is still frequently carried out, this is due to the ease of submitting debt applications and without any guarantees or certain conditions. Gold debt and receivable activities in Ujung Pulau Village only use the principle of trust, they are not written down, they are not dictated, without any witnesses involved so that the implementation of these debts and receivables triggers undesirable events (defaults). In the implementation of debts and receivables in Ujung Pulau Village, one party suffered a loss because the payment was replaced with cash equal to gold when borrowed. So the implementation of gold debts and receivables in Ujung Pulau Village has not been in accordance with what is recommended in Q.S Al-Baqarah verse 282 and has not implemented the principles of Islamic economics, namely the principle of monotheism, the principle of balance and the principle of justice. The solution to avoid usury from gold debts and receivables is to better understand and pay attention to the implementation of gold debts and receivables based on Islamic law. Keywords: Gold Debts and Receivables, Islamic Economics